Ethnic Chinese Retail Trade Activities in Banyuwangi in 1967-1998 - Febryaningrum, Levi; Sumarjono, Sumarjono; Na'im, Mohamad; Swastika, Kayan; Pratama, Akhmad Ryan; Jamil, Robit Nurul (JURNAL HISTORICA, 2022)
This article discusses the retail trading activities of ethnic Chinese in Banyuwangi in 1967-1998. During this period, various restrictive regulations emerged among the Chinese. One of them is Cabinet Presidium Instruction No. 37/UN/IN/6/1967, which contains a ban on business and residence for foreign Chinese. This condition made retail trading activities to a halt due to the forcible sealing of stores. The outline of the problems studied in this study includes the background of the Chinese ethnic retail trade activity and the formation of the ethnic Chinese retail trade network in Banyuwangi in 1967-1998. The research method used is the historical method which consists of heuristics, criticism, interpretation and historiography. The approach used is an economic sociology approach. The results of the study show that ethnic Chinese are increasingly developing their business by acting as retail traders due to limited capital and no special skills are needed. The establishment of a retail trade network is based on the nature of trust and shared experiences, using the concept of family and ethnic networks. The available commodities are diverse, reflecting the needs of the community and showing the development of the socio-economic life of the people in Banyuwangi.